2011
DOI: 10.1097/rti.0b013e3181ebeaba
|View full text |Cite
|
Sign up to set email alerts
|

Extrapleural Hematomas

Abstract: EPHs occur most commonly in high-energy blunt trauma; concomitant injuries are the rule, especially rib fractures. Biconvex hematomas tend to be large, likely resulting from high-pressure bleeding. Consequently, biconvex EPHs more often require surgical intervention. Nonconvex hematomas can usually be managed conservatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Extrapleural hematomas occur in approximately 7% of patients with blunt chest injuries [1]. These patients almost always have complications of rib fractures and hemothorax [1, 2]. Hemothorax after thoracic trauma can result in serious conditions, such as hemorrhagic shock.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extrapleural hematomas occur in approximately 7% of patients with blunt chest injuries [1]. These patients almost always have complications of rib fractures and hemothorax [1, 2]. Hemothorax after thoracic trauma can result in serious conditions, such as hemorrhagic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Several cases of conservative treatment for extrapleural hematomas including observation or image-guided drainage have been reported [3, 4]. Regarding the indications for surgical treatment, Chung et al reported that a biconvex extrapleural hematoma on CT tended to be larger than other types (nonconvex), and surgical intervention might be necessary [2]. Rashid et al also reported a single case of a patient who underwent surgical treatment with thoracotomy following insufficient needle aspiration drainage, while conservative treatment with observation and chest X-ray monitoring was performed in the remaining 33 patients with extrapleural hematomas [1].…”
Section: Discussionmentioning
confidence: 99%
“…Based on CT findings, Chung et al. 6 classified EH as bi-convex, commonly caused by arterial bleeding, and non-convex, a smaller volume associated with venous bleeding. Treatment options depend on the patient's clinical condition.…”
Section: Discussionmentioning
confidence: 99%
“…Stenosis of the brachiocephalic vein in association with high venous flow rates can increase venous pressure in the intercostals and bronchial veins of the chest, which in turn could alter local hemodynamics. As pleural fluid resorption is poor in normal conditions, excess pleural fluid formation is expected to occur, leading to unilateral pleural effusion on the same side as that of vein stenosis/thrombosis [ 5 ]. Therefore, the hematoma collected in the extrapleural space instead of the pleural one is putative because of a previous pleuritis with fusion of the two pleuric layers.…”
Section: Case Presentationmentioning
confidence: 99%